Spiritualiteit in het Lucasevangelie: geschiedenis en bevrijding - H. Welzen (Acta Theologica)
This first article of a series of three is about the spiritual nature of the gospel of Luke as a historiography. Luke presents his work as a history guided by God in which the reader of his book participates. God takes initiative in history to liberate the people of God and each of its members. The liberating character of this divine initiative is revealed in the ministry of Jesus as a Davidic king and as a prophet. At the same time the texts about Jesus as a prophet show the consequences of accepting or refusing the offer of God. In addition it becomes clear that the prophet who announces the divine liberation risks his life. The last section describes the semantic content of liberation as a theme in the gospel of Luke: it is about liberation from death and threats to life, from illness and demonical possession, from social and economic marginalization, from oppressive sabbatical laws, from everything that obstructs the alliance with God and traps one in the snares of Satan.